Accuracy of a Portable Indirect Calorimeter for Measuring Resting Energy Expenditure in Individuals With Cancer. Issue 1 (5th June 2018) - Purcell, Sarah A.; Elliott, Sarah A.; Ryan, Aoife M.; Sawyer, Michael B.; Prado, Carla M.
Abstract: Background: Determining optimal caloric intake for an individual with cancer is complicated by metabolic changes that occur, namely, alterations in resting energy expenditure (REE). There is currently no validated clinically available equation or tool to measure energy expenditure in these patients. Methods: Patients with newly diagnosed solid tumors underwent REE assessments using the FitMate GS portable indirect calorimeter and reference VMax metabolic cart; both used canopy hoods. REE was also estimated from the Harris‐Benedict, Mifflin St. Jeor, and Henry equations for comparison. Data were analyzed using paired samples t ‐test and the Bland‐Altman approach to assess group‐level and individual‐level agreement compared with the metabolic cart. Results: A total 26 patients (19 males; body mass index: 27.8 ± 5.5 kg/m 2 ; age: 62 ± 10 years) participated in the study. Biases for the FitMate GS and both equations were low (ranging from −44 to −92 kcal or −2.3% to −5.1%), indicating good group‐level accuracy. The FitMate GS had low bias, but the widest limits of agreement (−28.0% to 21.2%) compared with the 3 equations (Harris‐Benedict: −15.8% to 11.2%; Mifflin St. Jeor: −17.1% to 6.9%; Henry: −15.4% to 11.5%). These differences were not due to volume of oxygen, BMI category, or sex. Conclusion: FitMate GS performed well on a group level, but its accuracy was poor on an individual level. Further research should develop better equations and validate tools to measure energy expenditure for accurate dietary recommendations for patients at nutrition risk.